HUBUNGAN AKTIVITAS FISIK, KONSUMSI MAKANAN TINGGI LEMAK, TINGGI GARAM DAN PERILAKU MEROKOK DENGAN KEJADIAN HIPERTENSI PADA USIA PRODUKTIF (15-64 TAHUN) - Leonardi, Dicky (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2024)
Based on WHO data, the prevalence of hypertension sufferers currently shows around 1.13 billion people in the world. The prevalence of hypertension continues to increase in Indonesia, based on the results of the 2013-2018 Riskesdas prevalence of hypertension, from 25.8% to 34.1%. The purpose of this study was to determine the relationship between physical activity, consumption of foods high in salt, consumption of foods high in fat and smoking habits with the incidence of hypertension in productive age. This research method is using a systematic review. The population in this study is the population of productive age (15-64 years). The sources of literature in this study from Google Scholar, DOAJ, Garuda Ristekbrin. The results of this study that have been carried out have obtained 10 articles, where articles discussing the relationship between physical activity and the incidence of hypertension in productive age 3 of 5 articles stated that there was a relationship, as many as 6 of 8 articles stated that there was a relationship between consumption of high-salt foods and the incidence of hypertension in productive age, as many as 2 of 5 articles stated that there was a relationship between consumption of high-fat foods and hypertension of productive age, and 4 of 7 articles stated that there was a relationship between smoking habit and the incidence of hypertension in productive age. The conclusion is that there is a relationship between physical activity, consumption of high-salt foods with the incidence of hypertension in productive age, while consumption of high-fat foods has no relationship, and smoking habits are balanced.